Evaluation of Perceived Possible Outcomes in Patients Treated with Mandibular Distal Extension Partial Removable Dental Prostheses - Shammas, Mohammed; Wali, Othman; Alamoudi, Renad; Alharbi, Reem; Nasser, Maryam; Zahran, Lamar; Shetty, Karunakar; VT, Abdurahiman (Journal of Dentistry Indonesia, 2022)
Objectives: This study evaluated the perceived positive and negative general and oral health outcomes of patients after using mandibular distal extension partial removable dental prostheses (PRDPs) and assessed the effect of recall procedures on the treatment outcomes. Methods: A questionnaire comprising 20 items, pertaining to perceived positive and negative outcomes related to the patients’ perception scores after using mandibular distal extension PRDPs, was designed. The patients were recalled 1 week and 3 months after the insertion of the mandibular distal extension PRDPs. The perception scores were obtained, and the mean values calculated at 1 week and 3 months were compared using the paired t-test. Results: A significant difference in the mean scores was observed for the perceived positive outcomes (p = 0.018) but not for the perceived negative outcomes at 1 week and 3 months. Most patients agreed or strongly agreed with the statements concerning the perceived positive outcomes and disagreed or strongly disagreed with those concerning the perceived negative outcomes after 3 months. Conclusion: Most patients were satisfied with their mandibular distal extension PRDPs in terms of the perceived positive outcomes and disagreed with the statements concerning the perceived negative outcomes. The questionnaire was deemed appropriate for measuring the patients’ perceptions about the possible outcomes of using mandibular distal extension PRDPs.